GABA—from Inhibition to Cognition: Emerging Concepts. (October 2018) - Schmidt-Wilcke, T.; Fuchs, E.; Funke, K.; Vlachos, A.; Müller-Dahlhaus, F.; Puts, N. A. J.; Harris, R. E.; Edden, R. A. E.
Neural functioning and plasticity can be studied on different levels of organization and complexity ranging from the molecular and synaptic level to neural circuitry of whole brain networks. Across neuroscience different methods are being applied to better understand the role of various neurotransmitter systems in the evolution of perception and cognition. GABA is the main inhibitory neurotransmitter in the adult mammalian brain and, depending on the brain region, up to 25% of the total number of cortical neurons are GABAergic interneurons. At the one end of the spectrum, GABAergic neurons have been accurately described with regard to cell morphological, molecular, and electrophysiological properties; at the other end researchers try to link GABA concentrations in specific brain regions to human behavior using magnetic resonance spectroscopy. One of the main challenges of modern neuroscience currently is to integrate knowledge from highly specialized subfields at distinct biological scales into a coherent picture that bridges the gap between molecules and behavior. In the current review, recent findings from different fields of GABA research are summarized delineating a potential strategy to develop a more holistic picture of the function and role of GABA.